A ÁLGEBRA DOS VITRÔS – OBJETO DE APREDIZAGEM PARA O ENSINO DA ÁLGEBRA - Marchesan, Raquel C.; Milani, Leonogildo H.; Mecking, Gustavo T.; Soares, Carine G. T.; Konageski, Dionatam M. F.; Pereira, Tânia M.; Brizzi, Maristela L. S. (Salão do Conhecimento, 2013)
Resumo